ADR databases for on‐site clinical use: Potentials of summary of products characteristics. Issue 4 (24th February 2021) - Eiermann, Birgit; Rodriguez, Daniel; Cohen, Paul; Gustafsson, Lars L.
Abstract: Adverse drug reactions (ADRs) for all drugs in Europe are described in the legally approved Summary of Product Characteristics (SmPC). An overview of all ADRs of the patients' drug list can support healthcare staff to link patient symptoms to possible ADRs. We review the possibilities and challenges to extract ADR information from SmPCs or American Structured Product Labels and present the development of our semi‐automated procedure for extraction of ADRs from the tabulated section in the SmPCs to create a database, named Bikt, which is regularly updated and used at point of care in Sweden. The existence of five major table formats for ADRs used in the SmPCs required the development of different parsing scripts. Manual checks for correctness for all content have to be performed. The quality of extraction was investigated for all SmPCs by measuring precision, recall and F1 scores and compared with other methods published. We conclude that it is possible to semi‐automatically extract ADR information from SmPCs. However, clear technical and content guidelines and standards for ADR tables and terms from drug registration authorities would lead to improved extraction and usability of ADR information at point of care.